Exploratory study to evaluate the entrepreneurship ecosystem in Namibia's manufacturing sector - Maponga, Chivimbiso C J L (Research of GSB, 2018)
This study sought to explore what is termed the 'entrepreneurial ecosystem' that exists for small businesses operating in the manufacturing sector in Namibia. The objectives were to establish whether there exists a conducive business environment – that is an environment conducive for small businesses in the manufacturing sector to develop networks and build new institutional capabilities. The study also sought to determine if there existed an environment conducive to foster cooperation between different stakeholders in the manufacturing sector in Namibia. Finally the research also sought to make practical recommendations on how stakeholders in the small business sector in Namibia can create an integrated holistic system that encourages a healthy entrepreneurship ecosystem. Through an analysis of literature information provides an overview of the business environment, and through analysis of the primary findings, the researcher shares perception on the ecosystem from the manufacturers themselves. The interviews revealed that the challenges faced by small businesses operating in Windhoek were similar to those documented by existing literature. Of key note however, was the increasing perception of a lack of cooperation between various stakeholders, the government, the private sector, tertiary institution and consumers to make concerted efforts to foster a conducive environment for these small businesses. It is recommended that government initiatives be supported by the private and civil sector – particularly and awareness of and access to funding opportunities, compulsory skills development and training, and capacity building through mentorship and incubation and facilitating market access. The research concludes by suggesting a systematic model that illustrates the relationships (as suggested by the theory and the interviews) between the elements of the ecosystem, as well as recommendations for future research.